Iron kissed eaudiobook - Briggs, Patricia (Mercy Thompson, 2009)
Meet car mechanic and coyote shapeshifter Mercy Thompson, star of Patricia Briggs's #1 New York Times bestselling series. Being a lowly "walker" in a world of vampires, werewolves, and fae once kept her safe. But Mercy's bark-and bite-are not so harmless any more...   Though Mercy Thompson can shift her shape into that of a coyote, her loyalty never wavers. So when her former boss and mentor, Zee, asks for her help, she's there for him. A series of murders has rocked a fae reservation, and Zee needs her unique gifts, namely her coyote sense of smell, to sniff out the killer. But when Zee is accused of murdering the suspect Mercy outed, he's left to rot behind bars by his own kind. Now it's up to Mercy to clear his name, whether he wants her to or not. Mercy's loyalty is under pressure from other directions, too. Werewolves are not known for their patience, and if Mercy can't decide between the two she cares for, Sam and Adam may make the choice for her...